Endoplasmic reticulum stress aggravates ferroptosis via PERK/ATF4/HSPA5 pathway in UUO-induced renal fibrosis - Huang, Zhigang; Zhou, Lihua; Liu, Bin; Li, Xiaoju; Sang, Yu (Frontiers in Pharmacology, 2025)
Renal fibrosis, resulting from the transformation of damaged tubular epithelial cells (TECs), serves as a prevalent pathological condition observed in nearly all forms of advancing chronic kidney disease (CKD). Although crucial in fibrotic diseases, the association between endoplasmic reticulum stress (ERS) and ferroptosis remains incompletely elucidated. Herein, increased levels of heat shock protein family A member 5 (HSPA5), acting as a co-molecular in ERS and ferroptosis, along with EMT-associated alterations, including increased α-smooth muscle actin (α-SMA) and Col1a1 levels and decreased E-cad expression, were observed in fibrotic kidneys of Unilateral Ureteral Obstruction (UUO)-induced mouse models and TGF-β-induced EMT in HK-2 cells. The employment of ferrostatin-1 (Fer-1) improved these alterations and reversed TGF-β-induced EMT in vitro. More importantly, Inhibiting ERS by Tauroursodeoxycholate (TUDCA) reversed the alterations of ferroptosis, including GPX4 expression, reactive oxygen species (ROS) accumulation, iron overload, increased lipid peroxidation production, as well as EMT progression in vivo and in vitro. Whereas the overexpression of HSPA5 strikingly attenuated the inhibitory effects of TUDCA on ferroptosis and TGF-β-induced EMT in vitro. Mechanistically, Co-immunoprecipitation (Co-IP) tests showed that ATF4 engaged with and SUMOylated HSPA5 to trigger the HSPA5 signaling pathway in response to TGF-β. These findings illuminate that focusing on HSPA5 may present a promising therapeutic approach to enhance tubular epithelial cells’ survival and alleviate the progression of CKD.